2020
DOI: 10.3390/ijerph17196998
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Seasonality of Ambient Particles (PM2.5) in the City Centre of Addis Ababa

Abstract: Ambient air pollution is a growing public health concern in major African cities, including Addis Ababa (Ethiopia), where little information is available on fine particulate matter (PM2.5, with aerodynamic diameter <2.5 µm) pollution. This paper aims to characterize annual PM2.5, including bulk composition and seasonal patterns, in Addis Ababa. We collected 24-h PM2.5 samples in the central city every 6 days from November 2015 to November 2016. The mean (±SD) daily PM2.5 concentration was 53.8 (±25.0) µg/m3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…Similar concentration trends were observed in a chemical analysis-based source apportionment study with samples collected at one station (Tefera et al, 2020). Since that paper discusses results from only one location, it is not possible to generalize the results for the city airshed, but the presence of higher organic and black carbon components supports the conclusion of higher contributions from biomass and diesel combustion, followed by dust from the presence of crustal elements in the collected samples.…”
Section: Figure 14 Modeled Source Contributions To Annual Average Pm25 Pollution In Addis Ababasupporting
confidence: 63%
See 2 more Smart Citations
“…Similar concentration trends were observed in a chemical analysis-based source apportionment study with samples collected at one station (Tefera et al, 2020). Since that paper discusses results from only one location, it is not possible to generalize the results for the city airshed, but the presence of higher organic and black carbon components supports the conclusion of higher contributions from biomass and diesel combustion, followed by dust from the presence of crustal elements in the collected samples.…”
Section: Figure 14 Modeled Source Contributions To Annual Average Pm25 Pollution In Addis Ababasupporting
confidence: 63%
“…There was also a short AQ monitoring and research from November 2015 to November 2016, where the research collected 24-hour PM2.5 samples in AA's city center every 6 days. Its results show that the mean (±SD) daily PM2.5 concentration was 53.8 (±25.0) µg/m3, with 90% of sampled days exceeding the WHO's guidelines (Tefera et al, 2020). Typically, it is not expected to see highs in PM2.5 during the rainy months (Jun-Jul-Aug), but the trend in AA is an aberration which can be linked to lower surface temperatures, lower mixing layer heights and wind speeds under 2 m/s causing limited dispersion of emissions.…”
Section: Evaluation Of Aq In Aamentioning
confidence: 99%
See 1 more Smart Citation
“…Published and unpublished data from Ethiopia has shown that ambient fine PM (PM 2.5 —PM ≤ 2.5 microns in aerodynamic diameter) are high and above the Air Quality Guidelines (AQG) of the World Health Organization (WHO) [ 3 , 4 , 12 ]. Prior studies, for instance, in Addis Ababa [ 5 , 13 ] reported that PM 10 concentrations were increasing and above the annual value of WHO air quality guidelines [ 14 ] and Ethiopian standards [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In each country, the SANA included a systematic review of secondary data from peer‐reviewed literature, thesis reports from academia, government and national statistical reports, as well as limited primary data based on key informant interviews from major stakeholders to identify ongoing monitoring efforts, regulatory and policy needs, and political engagement. Through the country‐specific SANA process, critical gaps in research, policy frameworks, and implementation were identified spanning OSH, air pollution, and climate change across the region (Berhane, Kumie, Afullo, et al., 2016; Kumie et al., 2016; Mitike et al., 2016; Simane et al., 2016; Tefera et al., 2020). The SANA process informed the development of the initial paired research and training aims of the Eastern Africa Hub.…”
Section: Introductionmentioning
confidence: 99%